Simulation of radiated emission by shielded power feeders for electric propulsion of aircraft - Lansink Rotgerink, J.H.G.J. (IEEE, 2023)
Hybrid electric propulsion as one of the solutions towards sustainable aviation brings on-board a powertrain with high power levels, voltages and currents. In terms of electromagnetic compatibility this will inevitably raise conducted and radiated emission challenges. Power feeders may become a maj or source of electromagnetic radiation. This paper uses combined multiconductor transmission line and Hertzian Dipole methods to predict such radiated emissions of three-phase power feeders that include shielding. Results of simulated radiated emissions of a shielded trefoil cable are compared to full-wave simulations, models from literature, as well as measured results. Finally, the method is combined with simulated currents in a Simulink model of an electric powertrain, to obtain predicted in-situ radiated emissions of a shielded AC power feeder.